Novel concept of renewables association with synchronous generation for enhancing the provision of ancillary services. (1st November 2018) - Attya, A.B.; Anaya-Lara, O.; Leithead, W.E.
Highlights: Novel concept to associate renewables with conventional generation. It is adaptable to the controls of renewables' farms, converter stations and units. It is applied to enable the provision of voltage support by converter stations. It is also applied to provide frequency support by wind turbines. The proposed implementation method avoids frequency measurements. Abstract: Renewable energy sources are foreseen as a provider of full range of ancillary services. An innovative concept of alignment between renewable power generation elements and synchronous generators is proposed: Renewables Association with Synchronous generators (RAS). It mitigates the dependence on direct frequency measurements, which are prone to noise and lack of accuracy, and enables perfect coordination between the responses of renewable and conventional power plants. RAS relies on a leader synchronous generator, connected at the point of common coupling of the renewable power plant or close to it. This synchronous generator is able to provide ancillary services (e.g. frequency support and reactive compensation). The renewable power plant is controlled to provide such services similar to the leader synchronous generator, but scaled down/up to match the rating of the renewable power plant by integrating supplementary controllers that are associated with the synchronous generator response. Two approaches are proposed to provide voltage support, besides a supplementary frequency support controller. These RAS-based voltage and frequency support methods are compared to other methods proposed in the literature. Results show the positive impact of RAS concept on the provision of active power and reactive compensation to tackle frequency and voltage events respectively, following the response of the leader synchronous generator. DIgSILENT PowerFactory is the applied simulation environment.